Synthesis of hydroxylated pyrrolidines by allenic cyclisation. Issue 41 (13th October 2016) - Ng, Pearly Shuyi; Bates, Roderick W.
Abstract: The diastereoselective gold(I) catalysed cyclisation of highly substituted aminoallene derivatives allows the synthesis of both epi -DAB-1 and di- epi -lentiginosine. While the sense of stereoselectivity observed is in line with earlier observations on analogous piperidine-forming cyclisations, different ligands and reaction conditions are required to obtain good yields. Graphical abstract: